Cenografia e autoria em Campo Geral - Fossey, Marcela Franco [UNESP] (Universidade Estadual de Maringa, 2012)
The analyses of Guimarães Rosa's works often consider relevant facts connected to the author's personal life: his childwood in Sertão of Minas Gerais and his posterior wanderings through this region, his medical and diplomatic career, his deep knowledge of several languages, his misticism. His literary work would be a quite faithful reflection of his life. In this work, an analysis of Campo Geral (1956) [1977], considered by many critics as an autobiographical novel, is proposed, aiming to conciliate the inevitable influence of the author's biographical life without confounding or mixing enunciation scene with historical situation. Therefore, it was taken into account concepts of scenography, paratopia and of person-writer-inscriber, as proposed by Maingueneau (2006).
Scenography and authorship in Campo Geral
Keywords: Enunciation scene; Guimarães Rosa; Paratopia